TRANSPOR ION TEMBAGA (II) MELALUI TEKNIK MEMBRAN CAIR FASA RUAH - Tetra, Olly Norita; Alif, Admin; A, Hermansyah; -, Emriadi (Jurnal Riset Kimia, 2007)
ABSTRACT Bulk liquid membrane methode have been used to study transport  of  Cu(II) ion containing oxine as carrier. It was found that total Cu(II) ion 20 ppm was transported from source phase to receiving phase after 360 min reached 97.3 % in optimum conditions source phase pH is 3, oxine concentration as carier in membrane phase is 17.5 x 10-4 M, membrane volume is 20 mL, sulfur acid concentration in receiving phase 0.15 M and time of balance is 15 minute. Thus a pH gradient is utilized to drive the Cu(II) transport.